Literature Review: The Effect of the Creative Problem Solving (CPS) Learning Model on Students' Creative Thinking Ability - Milanda Viona Delfiza; Rahmadhani Fitri; Sa'diatul Fuadiyah (Bioeducation Journal, 2023)
In the context of the 21st century, we are basically required to have skills. in the world of education itself, skills can be realized with learning media based on the Higher Order of Thinking Skills (HOTS). this is a challenge for educators, in improving the skills and creativity of each student. Basically the creative problem solving model is an ability related to problem-based creativity. The purpose of this research itself is to prove that the Creative problem solving model can be an effort to improve students' creative thinking skills. The research was conducted with a literature review on related articles within a five year period (2018-2022). From 20 literatures, 5 of the most suitable ideas were taken, proving that creative problem solving is a very good model to be developed and has a positive influence in improving students' creative thinking abilities.